(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
The combination of fuzzy logic tools and multi criteria decision making has a great relevance in the literature. Real life decision making problem under uncertainty is usually associated with information that may be incomplete or imprecise. The information on which decisions are based is uncertainty . Decision making theory is based on several type of uncertainty and tools. Computing with word (CwW) is very effective tool for decision making. Professor Zadeh the creator of CwW idea , formulated many challenge problems. Zadeh’s flight delay problem using relative-distance-measure is discussed in [1].In this paper RDM is applied to solve real life decision making problem. A numerical example is used to illustrate the procedure of the presented approach.